2018
DOI: 10.1002/ehf2.12341
|View full text |Cite
|
Sign up to set email alerts
|

Telbivudine in chronic lymphocytic myocarditis and human parvovirus B19 transcriptional activity

Abstract: AimsMyocarditis is often associated with parvovirus B19 (B19V) persistence, which can induce vascular damage. Based on the antiviral and anti‐inflammatory properties of telbivudine, we aimed to evaluate its efficacy to protect B19V‐infected endothelial cells in vitro and to treat chronic lymphocytic myocarditis patients with B19V transcriptional activity.Methods and resultsWe evaluated the endothelial‐protective potential of telbivudine in human microvascular endothelial cells‐1, which were infected with B19V.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 52 publications
(98 reference statements)
0
32
0
Order By: Relevance
“…31 ). B19V infection of endothelial cells can thereby induce cardiomyocyte apoptosis, as shown in vitro in B19V-infected endothelial cells co-cultured with cardiomyocytes 32 . Sustained severe cardiac inflammation, especially in the setting of acute B19V infection, might lead to cardiomyocyte necrosis 33 .…”
Section: Adenoviruses and Enterovirusesmentioning
confidence: 93%
“…31 ). B19V infection of endothelial cells can thereby induce cardiomyocyte apoptosis, as shown in vitro in B19V-infected endothelial cells co-cultured with cardiomyocytes 32 . Sustained severe cardiac inflammation, especially in the setting of acute B19V infection, might lead to cardiomyocyte necrosis 33 .…”
Section: Adenoviruses and Enterovirusesmentioning
confidence: 93%
“…There is no Food and Drug Administrationapproved regimen for the treatment of acute and chronic myocarditis. 2,23,29,30,32,34,36,37,41,42,78,85,89,136,147,177,[187][188][189][190][191][192][193][194][195] Still, consideration is reserved for patients with newonset, rapidly deteriorating, advanced heart failure with suspicion of the following conditions:…”
Section: Immunosuppressive Therapymentioning
confidence: 99%
“…16,19,77,196 Further studies to investigate the utility of novel tools for the analysis of EMB and improvement of diagnostic and prognostic assessment of myocarditis by means of transcriptomic, proteomic or genetic analysis have shown promising results. 71,86,99,100,187…”
Section: Prognosis and Outcomementioning
confidence: 99%
“…Moreover, telbivudine has some pleiotropic immunomodulatory and anti-inflammatory properties (Rehermann and Bertoletti, 2015). Recently, it was shown that telbivudine confers endothelial-protective effects on B19V-infected endothelial cells and improves the chronic myocarditis associated with B19V transcriptional activity (Van Linthout et al, 2018).…”
Section: Introductionmentioning
confidence: 99%